Revisiting Arms Race between India and Pakistan: A Case of Asymmetric Causal Relationship of Military Expenditures. Issue 6 (17th August 2020) - Amir-ud-Din, Rafi; Waqi Sajjad, Fatima; Aziz, Shazia
ABSTRACT: Pakistan and India have been arch-enemies since their independence from the British Rule. There have been over four full-fledged armed conflicts, countless border skirmishes and cross-border ceasefire violations between these neighbouring countries. Their mutual relationships have often nosedived to a point where the nuclear conflagration seemed real possibility. While India is among the five largest military spenders in the world, Pakistan spends a disproportionately larger share of its GDP on defence to neutralize the Indian military advantage. While Pakistan's military expenditure is largely India-specific, it is not clear if the reverse is also true. Therefore, this study explores if the military expenditure of India and Pakistan are causally associated with each other or the arms race is asymmetric. Using the maximum entropy bootstrapping method and a series of robustness checks, we find that while military expenditure of Pakistan is shaped by the Indian military expenditure, the military expenditure in India is not Pakistan-specific. This study has important policy implications for the region because Pakistan may explore alternative strategic relationships with India. A revision of strategic relationship between the two South Asian neighbours may help in the resolution of the long-standing political, social and economic problems of both the countries.